Description of four new species of brachypterous Encyrtidae (Hymenoptera: Chalcidoidea) from India - Hayat, Mohammad; Veenakumari, Kamalanathan (Zootaxa, 2015)
Four new brachypterous species of Encyrtidae (Hymenoptera: Chalcidoidea) are described. These are: Astymachus eximius Hayat, sp. nov., Ixodiphagus aethes Hayat, sp. nov., Monstranusia brachyptera Hayat, sp. nov., Ooencyrtus notialis Hayat, sp. nov. Brachyptery in the genera Astymachus Howard and Monstranusia Trjapitzin is reported for the first time.